The collection emagazine (The Collection.)
The Collection is a showcase of the best that SEE region has to offer in terms of lifestyle, travel and tourism and acts as the penultimate business card to introduce the region to potential tourists and investors. Don’t miss your chance to join the real club of ‘who is who’ in the region where we introduce the world to the best of Montenegro, Serbia, Croatia, Bosnia & Herzegovina, Slovenia, Albania, North Macedonia and other European countries in one unique publication. In this 36th edition of our prestigious magazine, we have placed an additional emphasis on the rich array of luxurious novelties that characterize this winter/spring period.